Pengembangan Sistem Informasi Manajemen Reproduksi Sapi Perah Balai Besar Pelatihan Peternakan (BBPP) Batu - Ians Adji Adhitama; Issa Arwani; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Balai Besar Pelatihan Peternakan Batu is one of the technical implementation units (UPT) in the field of training under the Indonesian Ministry of Agriculture. Based on the results of the initial survey and the results of an interview with one of the employees there, BBPP Batu does not yet have a special information system for dairy cows in the area. Currently, the dairy cattle reproduction management process there is still using the recording process using a reproduction card that is written manually. These reproduction cards are sometimes borrowed by trainees and not returned. The fact stated by Dollar (2014) proves that there is an improvement in reproductive performance as long as there is a good reproductive management system. In overcoming the above problems, a solution was made in the form of a dairy cattle management information system which was built using the SDLC Prototyping method. At the analysis and design stage, a model is built that can facilitate communication between developers and stakeholders in order to find the best solution in the form of a web and Android-based information system. The models used in the analysis and design stages include use cases, use case scenarios, sequence diagrams, class diagrams, and relational models. The system that has been built will be tested using BlackBox testing, compatibility testing, and user-acceptance testing. Blackbox testing produces valid results in all tests. The results of Compatibility testing on web applications using SortSite5 is that all the browser that has been tested can run the reproduction management information system with some major and minor problems. For android applications, applications can run on Android API 19 (KitKat) and above. Then on UAT testing of actors and stakeholders, the resulting value of 100% acceptance of the system that was built indicates that the system can be accepted by stakeholders.